Forced Convection Heat Transfer Using Water-Ethylene Glycol (60:40) Based Nanofluids in Automotive Cooling System - N. A., Usri (Universiti Malaysia Pahang, 2015)
Coolant has an important role in stabilizing the temperature of automotive components to prevent damage and failure. As a new class of thermal fluid, nanofluids as a coolant was introduced and its heat transfer coefficient performance is studied. This paper evaluates and analyzes the convective heat transfer coefficient of 60: 40 water-ethylene glycol based nanofluids. Nanofluids are prepared using dilution technique for Titanium Oxide (TiO2) in 60:40 (water: ethylene glycol) mixture. The experiments were conducted at a constant heat flux boundary under turbulent region with the Reynolds number more than 10,000 and working temperature of 70 oC for application in automotive cooling system. It was found that the heat transfer coefficient of the nanofluids enhanced with increased concentration. As a conclusion, the optimum heat transfer enhancement of TiO2 nanofluids is observed as 33.9 % higher than base liquid of water-ethylene glycol (60:40) mixture at 1.5 % volume concentration. This paper recommend to use Titanium Oxide with 1.0 % and 1.5 % volume concentration dispersed in 60:40 water-ethylene glycol mixture base for automotive cooling system.